Tanggung Jawab Negara Terhadap Pemenuhan Hak Atas Kesehatan Masyarakat Indonesia dalam Pelaksanaan Test Covid-19 Ditinjau dari International Covenant On Economic, Social, And Cultural Rights (ICESCR) - Shantika Hasintongan; Danial Danial; Surya Anom (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
The right to health is part of human rights. Health is closely related to everyday human life. The availability of health services and medicines, a clean and healthy environment, and other matters related to health are vital factors for human survival. In the COVID-19 pandemic situation, health is a basic need for all levels of society. The problems are, how the state's responsibility to fulfill the right to health in the conditions of the COVID-19 pandemic for the Indonesian people and how to fulfill the right to health for the Indonesian people in implementing the COVID-19 Test in terms of the International Covenant On Economic, Social , And Cultural Rights (ICESCR).This research uses Juridical-Normative by using the type of normative legal research data which is divided into primary legal materials, secondary materials and tertiary legal materials. The research analysis of this writing uses Descriptive-Qualitative and in collecting research data this research is obtained through library research and data access through journals, and the Internet.The results of this research are, first, the State has shown forms of responsibility in fulfilling the right to health in the conditions of the COVID-19 pandemic to the Indonesian people. providing test kits to detect the transmission of COVID-19 from several countries at varied and unaffordable rates for the public, issuing a package of rules as formal legitimacy for handling COVID-19, and giving orders to all people to comply with 3M, namely wearing masks, Wash your hands and keep your distance. Second, the fulfillment of the right to health for the Indonesian people in implementing the COVID-19 test has not been fulfilled by the State. The application of the nominal cost of the COVID-19 test is expensive, varied, and unaffordable for every element of society.